Langkah strategis pengembangan indigenous tourism: Studi kasus di Kabupaten Kepulauan Selayar - Ilham Junaid (Faculty of Social and Political Science, Universitas Airlangga, 2017)
Indigenous tourism is a relatively new concept for tourism stakeholders and has not become a priority to encourage local tourism potential. The lack of information and previous study about the concept of indigenous tourism and an understanding of the concept make tourism destination focused only in promoting local culture. Therefore, this research aims to identify: 1) the potential of Bitombang and Pandai Besi village in supporting indigenous tourism in Selayar Regency; 2) strategic steps required in supporting Selayar regency through indigenous tourism concept; and 3) actions to take for stakeholders to achieve development goals and achieving balance between indigenous tourism and sustainable tourism. Approach used in this study is feature of qualitative study which able to lead researcher in understanding indigenous tourism in Selayar Regency. To gather the data, researcher conducted interview to the society, government staff, and local communities in Selayar who possess adequate comprehension about the tourism circumstances, and Selayar people sociocultural condition. There are 8 choosen informants who are originally Selayar residents. The research shows that Bitombang and Pandai Besi Old Village are important assets in supporting the development of indigenous tourism, aside from another tourism potential. Therefore, study about history and cultural value of indigenous people, procurement of local tour guide, initiation from environmental organization, and travel route map for tourist are essential. Government’s role is also strongly expected to facilitate various communities to take part in the development of indigenous tourism.